Randomized evaluation of a novel, fixed-dose combination of perindopril 3.5 mg/amlodipine 2.5 mg as a first-step treatment in hypertension. Issue 3 (March 2015) - Laurent, Stéphane; Parati, Gianfranco; Chazova, Irina; Sirenko, Yuriy; Erglis, Andrejs; Laucevicius, Aleksandras; Farsang, Csaba
<x xml:space="preserve">Abstract</x> Objective: To evaluate perindopril 3.5 mg/amlodipine 2.5 mg once daily, a novel fixed-dose combination adapted for first-step treatment in patients with hypertension. This fixed dose had to be equivalent to amlodipine 5 mg in terms of blood pressure efficacy, but with an expected better tolerability profile. We selected two drugs with complementary modes of action, with doses chosen so that each drug would contribute similarly to the overall blood pressure-lowering effect Methods: An international, randomized, double-blind, placebo-controlled study with six equal parallel treatment arms and an 8-week randomized treatment period, whose design, clinical significance and non-inferiority criteria were in accordance with European guidelines. Results: In all, 1581 patients with mild-to-moderate uncomplicated hypertension (mean age 51.7 years) were randomized and 94.7% completed the study. The combination was statistically and clinically superior to placebo (between-group differences: SBP: −7.22 mmHg, DBP: −4.12 mmHg, P < 0.001 for both). Rates of response and normalization of blood pressure were greater with the combination (P < 0.001 for both) and numerical differences relative to placebo were apparent at 2 weeks. The combination was superior to either component given singly (P < 0.001 for both drugs, for SBP and DBP), and was non-inferior to both component drugs given singly at their lowest clinically-approved doses. The components of the combination had similar effects on SBP (perindopril 3.5 mg: −16.3 mmHg; amlodipine 2.5 mg: −16.0 mmHg). Adverse events relating to peripheral oedema were less frequent with the combination than with amlodipine 5 mg. Conclusions: The observed blood pressure-lowering efficacy, rapidity of onset of effect and favourable safety profile of the combination perindopril 3.5 mg/amlodipine 2.5 mg indicate its potential suitability for use as first-step treatment in hypertension.